Applying Project-Based Learning Based on Playful Learning in Primary Schools: A Study in Indonesia And Finland - Sujino Sujino; Herlina Herlina; Iva Sarifah (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to analyze the differences in the implementation of Project-Based Learning (PjBL) based on Playful Learning in elementary schools in Finland and Indonesia. The primary focus of the research is on planning, implementation, facilities, and the evaluation of the learning process. Data were collected through interviews, observations, and documentation conducted at two schools: Norden International School in Finland and SDN 06 Pahauman in Indonesia. The findings reveal significant differences between the two schools. At SDN 06 Pahauman, lesson planning is conducted simply and adapted to the limited facilities available. As a result, the Playful Learning approach cannot be fully maximized. However, the learning process still emphasizes hands-on experiences and active student involvement. In contrast, Norden International School benefits from advanced technological infrastructure, which supports digital-based projects. This allows for optimal creative exploration and collaboration during the learning process. Differences are also observed in the evaluation methods. SDN 06 Pahauman focuses primarily on the final project outcomes, whereas Norden International School employs both formative and summative evaluations, complemented by continuous feedback.